Effectiveness of laparoscopic appendectomy over open appendectomy in a tertiary care centre: a retrospective study - Akshitha, Gardas; Venkata Reddy, Morthala; Ananthula, Anusha (International Surgery Journal, 2023)
Background: Acute abdomen is the most common surgical clinical entity. Appendectomy is the treatment of choice for acute appendicitis. It can be done by open or laparoscopic method. Laparoscopic appendectomy gives a better evaluation of the peritoneal cavity than that obtained by open approach and also facilitates other differential diagnosis. Methods: Patients admitted under surgical unit from December 2020 to June 2022, at Mamata Medical College and Hospital, Khammam. A study was carried out on 100 patients were admitted with 50 patients undergoing laparoscopic appendectomy and the remaining 50 patients undergoing open appendectomy. ln both study groups the outcome was assessed based on the intra operative finding, operative time, post-operative recovery, post-operative complications, and length of hospital stay. Results: Findings of the patients undergoing open and laparoscopic appendectomy were compared and recorded. After analysing the data, there were significant differences between the two procedures with laparoscopic appendicectomy being better in respect to post operative pain perception, duration of analgesics used in days, postoperative infection, postoperative bleeding, post operative duration of hospital stay days and return to normal work in days with p value being significant. Conclusions: The laparoscopic appendicectomy was better than open appendicectomy with respect to pain score, lesser use of analgesics, post operative complications like vomiting, ileus and wound infection rate. Only drawback of laparoscopic appendicectomy was with the duration of surgery. Overall laparoscopic appendicectomy is better than open appendicectomy in selected patients with acute/recurrent appendicitis.